2012
DOI: 10.1371/journal.pone.0044425
|View full text |Cite
|
Sign up to set email alerts
|

A European Melting Pot of Harbour Porpoise in the French Atlantic Coasts Inferred from Mitochondrial and Nuclear Data

Abstract: Field surveys have reported a global shift in harbour porpoise distribution in European waters during the last 15 years, including a return to the Atlantic coasts of France. In this study, we analyzed genetic polymorphisms at a fragment of the mitochondrial control region (mtDNA CR) and 7 nuclear microsatellite loci, for 52 animals stranded and by-caught between 2000 and 2010 along the Atlantic coasts of France. The analysis of nuclear and mitochondrial loci provided contrasting results. The mtDNA revealed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 62 publications
5
28
0
Order By: Relevance
“…Hence, this suggests male dispersal in the breeding season for mating purposes which is a mechanism that could serve to avoid inbreeding as seen in other mammals (e.g., Handley and Perrin, 2007). Another explanation could be that the two populations are in the process of admixing, as Alfonsi et al (2012) suggested for the harbour porpoise along the French Atlantic coast. The lack of deviation from HW expectations of the microsatellite frequencies suggested a panmictic breeding population as it only takes one generation to restore HW-expectations after two genetically different populations admix.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, this suggests male dispersal in the breeding season for mating purposes which is a mechanism that could serve to avoid inbreeding as seen in other mammals (e.g., Handley and Perrin, 2007). Another explanation could be that the two populations are in the process of admixing, as Alfonsi et al (2012) suggested for the harbour porpoise along the French Atlantic coast. The lack of deviation from HW expectations of the microsatellite frequencies suggested a panmictic breeding population as it only takes one generation to restore HW-expectations after two genetically different populations admix.…”
Section: Discussionmentioning
confidence: 95%
“…Block et al, 2011). In the last decades, harbour porpoises (Phocoena phocoena) have been studied intensely in European waters to identify population delimitations and to monitor the status of the species (e.g., Siebert et al, 2006, Evans and Teilmann, 2009, Wiemann et al, 2010Alfonsi et al, 2012;Fontaine et al, 2014). The main driver for this effort has been the fact that several thousand harbour porpoises are bycaught each year and drown in European gillnet fisheries (Tregenza et al, 1997;Vinther and Larsen, 2004;Bjørge et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These results contrast with those from other areas within the global range of the harbour porpoise (e.g. Wang et al 1996, Wang & Berggren 1997, Rosel et al 1999, Chivers et al 2002, Tolley & Rosel 2006, Fontaine et al 2007, Wiemann et al 2010, Alfonsi et al 2012, De Luna et al 2012). In particular, Chivers et al (2002) suggested more subdivision of harbour porpoises within the same region that we studied.…”
Section: Population Structure Of Harbour Porpoisesmentioning
confidence: 59%
“…Some or all of these subspecies comprise a set of spatially structured populations (e.g. Wang et al 1996, Wang & Berggren 1997, Rosel et al 1999, Tolley & Rosel 2006, Fontaine et al 2007, Alfonsi et al 2012. To date, the majority of studies have focused on northeastern Atlantic and Baltic Sea population groups.…”
Section: Harbour Porpoisementioning
confidence: 99%
See 1 more Smart Citation